Effect of Plant Growth Regulators on the Growth and Yield of Capsicum (Capsicum annuum L.) - Kaur, Talvinder; Sharma, Ashutosh; Sharma, Sonika; Sharma, Neha; Sharma, Shivam (International Journal of Environment, Agriculture and Biotechnology, 2024)
An experiment was conducted in the experimental Farm of DAV University, Jalandhar during kharif, 2023 to assess the combined effect of plant growth regulators and varieties on growth and yield of capsicum. The experiment comprised of four treatments of plant growth regulators, (G0 = No growth regulator (control), G1= GA3 @ 50 ppm, G2= SA @ 50 ppm, G3= MeJa @ 2mM) and three varieties (V1=PSM-1, V2= F1- hybrid, V3= Orobelle) was replicated thrice and laid out in Randomized Block Design. Among plant growth regulators, maximum growth and yield parameters were observed in GA3 @ 50 ppm. Among the varieties, V1= PSM-1 were recorded to be the best regarding growth and yield parameters. For combined effect, G1V1 gave the highest growth and yield and G0V3 gave the lowest growth and yield. The highest gross return, net returns and cost benefit ratio was significantly observed in T1 (GA3 @ 50ppm × PSM-1) following by in T5 (GA3 × F1- hybrid). So, 50 ppm GA3 may be used for capsicum cultivation.